2023
DOI: 10.1007/s40843-022-2332-9
|View full text |Cite
|
Sign up to set email alerts
|

基于透明活性层的高效柔性半透明有机太阳能电池

Abstract: The flexibility and translucency aspects are unparalleled advantages of organic solar cells (OSCs), which have attracted great attention from the scientific and industrial communities. Currently, the key to improve the performance of flexible semi-transparent OSCs (ST-OSCs) lies in flexible transparent electrodes (FTEs) and the light-absorbing active layer. Herein, high-quality multi-layer FTEs with solarweighted transmittance of 84.8% are employed, which allows the photo-active layer to effectively capture li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Both the roofs and walls of greenhouse can be integrated with ST‐OSCs, which not only provide energy for agricultural management such as supplementary lighting, temperature regulation, and irrigation, but are also capable of transmitting sufficient light for plant growth. [ 54,55 ] Typically, plants capture solar photons using special pigments for photosynthesis and photomorphogenesis mainly in the 400–700 nm spectral range, [ 56,57 ] coinciding with the high transmission region of PP2/BTP‐eC9‐based ST‐OSCs (Figure 4c). Three crops, including pea seedlings and wheats grown in hydroponics, and corianders grown in soil cultivation, were chosen for cultivation based on vegetables, staples, and spices.…”
Section: Resultsmentioning
confidence: 99%
“…Both the roofs and walls of greenhouse can be integrated with ST‐OSCs, which not only provide energy for agricultural management such as supplementary lighting, temperature regulation, and irrigation, but are also capable of transmitting sufficient light for plant growth. [ 54,55 ] Typically, plants capture solar photons using special pigments for photosynthesis and photomorphogenesis mainly in the 400–700 nm spectral range, [ 56,57 ] coinciding with the high transmission region of PP2/BTP‐eC9‐based ST‐OSCs (Figure 4c). Three crops, including pea seedlings and wheats grown in hydroponics, and corianders grown in soil cultivation, were chosen for cultivation based on vegetables, staples, and spices.…”
Section: Resultsmentioning
confidence: 99%
“…[34] Domain sizes of intermixed amorphous phases (ξ) can be obtained by fitting the 1D GISAXS profile with the Debye-Anderson-Brumberger (DAB) model, while those of pure D/A phases (2R g ) can be estimated by fitting the 1D GISAXS profile with fractal-like networks. [33][34][35][36] In Figure 5a-c, Wang et al explored the influence of the 1-CN additive on the domain sizes of pure phases and intermixed amorphous phases in PTB7-Th:IHIC blend films by fitting the films' in-plane (IP) GISAXS profiles with fractal-like networks and DAB model, respectively. [37] Results revealed that the fitted 2R g values of PTB7-Th:IHIC blend films with and without 1-CN additive were similar (13.2 and 12.3 nm, respectively), while 1-CN additive incorporation could decrease the fitted ξ value from 23.6 to 19.1 nm.…”
Section: X-ray Scattering Techniquesmentioning
confidence: 99%
“…X-ray scattering techniques provide direct domain information and reveal the domain composition variation-J sc /FF correlation in OSCs. [24,33] Grazing incidence small-angle X-ray scattering (GISAXS) is a straightforward technique for characterizing the nanometer-scale domain size of each phase in OSCs, which requires a distance of several meters between sample and detector to ensure the parallel scattering and get the information on size scales of 10-100 nm. [34] Domain sizes of intermixed amorphous phases (ξ) can be obtained by fitting the 1D GISAXS profile with the Debye-Anderson-Brumberger (DAB) model, while those of pure D/A phases (2R g ) can be estimated by fitting the 1D GISAXS profile with fractal-like networks.…”
Section: X-ray Scattering Techniquesmentioning
confidence: 99%